3rd International Symposium on High-Temperature Metallurgical Processing : proceedings of a symposium sponsored by the Pyrometallurgy Committee and the Energy Committee of the Extraction and Processing Division of TMS (The Minerals, Metals & Materials Society), Held during the TMS 2012 Annual Meeting & Exhibition Orlando, Florida, USA March 11-15, 2012 - Jiang, Tao, 1963- (John Wiley & Sons, 2012)
Proceedings of a symposium sponsored by the Pyrometallurgy Committee and the Energy Committee of the Extraction and Processing Division of TMS (The Minerals, Metals & Materials Society) Held during the TMS 2012 Annual Meeting & Exhibition Orlando, Florida, USAMarch 11-15, 2012.
Keywords: Metals -- Effect of high temperatures on -- Congresses.; Light metals -- Metallurgy -- Congresses.; Alloys -- Congresses.; elektronické knihy; electronic books